Loosely synchronized activation of anterior cingulate cortical neurons for scratching response during histamine-induced itch - Chiwoo Lee; Jihae Oh; Jae-Hyung Lee; Bong-Kiun Kaang; Hyoung-Gon Ko (Molecular Brain, 2023)
Abstract Itch is a distinctive sensation that causes a specific affection and scratching reaction. The anterior cingulate cortex (ACC) has been linked to itch sensation in numerous studies; however, its precise function in processing pruritic inputs remains unknown. Distinguishing the precise role of the ACC in itch sensation can be challenging because of its capacity to conduct heterologous neurophysiological activities. Here, we used in vivo calcium imaging to examine how ACC neurons in free-moving mice react to pruritogenic histamine. In particular, we focused on how the activity of the ACC neurons varied before and after the scratching response. We discovered that although the change in neuronal activity was not synchronized with the scratching reaction, the overall activity of itch-responsive neurons promptly decreased after the scratching response. These findings suggest that the ACC does not directly elicit the feeling of itchiness.